Long-chain perfluoroalkyl carboxylic acids in Pacific cods from coastal areas in northern Japan: A major source of human dietary exposure. (April 2015) - Fujii, Yukiko; Sakurada, Tsukasa; Harada, Kouji H.; Koizumi, Akio; Kimura, Osamu; Endo, Tetsuya; Haraguchi, Koichi
Abstract: This study investigates perfluoroalkyl carboxylic acids (PFCAs) contamination of edible fish muscle from Japanese coastal waters. The concentrations of PFCAs with 8–14 carbon atoms (C8–C14) in Pacific cods in Hokkaido, Japan were 51 (median: pg/g-wet weight) for C8, 93 for C9, 99 for C10, 746 for C11, 416 for C12, 404 for C13, and 93 for C14. The levels of C9–C14 PFCAs in fish were strongly correlated to each other, but not to C8 and the other chlorinated persistent organic pollutants, indicating that C9–C14 PFCAs have a different emission source and/or bioaccumulation mechanism. The relative ratios between estimated PFCAs intake through fish consumption and the reported total dietary exposure of PFCAs were less than 1 for C8 to C9, but were more than 1 for C10 to C14. This result strongly suggests that fish consumption is a significant source of human dietary exposure to C10–C14 PFCAs. Highlights: Perfluoroalkyl carboxylic acids were detected in edible cod fish from Japanese coastal waters. The levels of long-chain PFCAs in fish were independent from those of C8 and other POPs. Long chain PFCAs intake through fish and the reported total dietary exposure were comparable. Sea fish such as Pacific cod may be a significant human dietary source of long-chain PFCAs. Abstract : Sea fish are a significant source of long-chain perfluoroalkyl carboxylic acids for the Japanese population.